New Concept of Teaching English to Students from Non-English Speaking Countries - Ratna Rintaningrum; Aleksandar Kavgić; Marina Garaeva; Lyudmila Shcherbatykh; Próspero Morán; Kundharu Saddhono; Olga Shalina; Larisa Vatutina; Olesya Dudnik; Mikhail Kosov (Ital Publication, 2023)
The objective of this study is to compare and underscore the advantages and disadvantages of learning English in non-English speaking countries to propose the concept of a new English teaching method for students from non-English speaking countries (the case of Russia, Spain, Serbia, and Indonesia). The study used a mixed-methods approach with qualitative analysis of literature from Russia, Serbia, Spain, and Indonesia, and a research questionnaire was developed. 1595 participants were recruited for a survey determining their experiences of learning English and students’ perspectives on English teaching methods in non-English speaking countries. The data went through thematic analysis in the qualitative part of the research and descriptive analysis in the quantitative survey-based design. Findings of the qualitative analysis revealed both advantages and disadvantages of teaching English to students in selected countries; however, the main findings reported the presence of cultural barriers and students finding it difficult to form meanings from the English language context. Conceptual thinking helped to understand the role of memory and comprehension when learning a foreign language, whereby research focuses on more novel concepts. Future researchers can focus on the area of neural development of students' memory, which can help guide strategies to teach the English language effectively. Doi: 10.28991/ESJ-2023-07-06-020 Full Text: PDF